Affective and Psychomotor Aspects of 5th-Grade Students in Online Learning against Students with Special Needs Spirit of Learning - Karina, Poppy Mega; Maryanti, Rina; Wulandary, Verra (JASSI ANAKKU, 2021)
This study aims to determine how the affective and psychomotor aspects of 5th-grade students of elementary school West Java, Indonesia with student special needs. This research method uses a qualitative descriptive method to 38 5th-grade students of elementary school West Java, Indonesia with student special needs. Data collection techniques in this study were in the form of surveys and questionnaires, namely filling out a questionnaire on a google form that had been prepared. The results of this survey stated that 90% of the students of elementary school West Java, Indonesia, 90% still often interacted with their families, did not tend to play games in their daily lives, students were still doing sports during the COVID-19 pandemic. To encourage children's psychomotor, all students are still enthusiastic when learning online, even students’ experience a decrease in enthusiasm when learning online compared to face-to-face learning. Overall, almost all students want to return to face-to-face learning directly to the school. These results indicate that the students' sense of enthusiasm for learning at elementary school.